Psychological violence at a multi-campus Further Education and Training College - Meyer, Helena Willme; Kirsten, Tiaan GJC (South African Journal of Higher Education, 2016)
Research indicates that those employed in the education sector are especially susceptible to psychological violence. This study aimed to determine the nature, more specifically the prevalence, severity and perpetrators of psychological violence at a multi-campus South African Further Education and Training (FET) College. A Psychological Violence Scale was developed and distributed to the study population of 262 staff members at six campuses and Corporate Centre of an FET College; 174 questionnaires were completed and returned. Findings indicated that staff members experienced psychological violence as prevalent, severe and mostly from superiors.